Solar Charger Controller Efficiency Analysis of Type Pulse Width Modulation (PWM) and Maximum Power Point Tracking (MPPT) - Elka Faizal; Yuniarto Agus Winoko; Mohammad Sukri Mustapa; Muhammad Kozin (CV. Creative Tugu Pena, 2022)
Solar radiation at any time can be different due to various things such as blocking of sunlight due to clouds, the intensity of the sun from sunrise to sunset, cloudiness in the rainy season, and the presence of fog in certain areas which causes different levels of solar energy. radiation that causes the output power of solar cells to vary. and not optimal. For that we need a control device that can stabilize the energy output from solar cells called Solar Charge Controller (SCC). This research was conducted to determine the value of the output power, voltage, and current of SCC type Type Pulse Width (PWM) and Maximum Power Point Tracking (MPPT), then determine the value of efficiency, and compare which type of SCC is better to use. Sampling of solar voltage and current data in the field at 10.00 – 15.00, this is because at that time the sunlight reaches its maximum intensity. The results showed that the MPPT type SCC efficiency was higher than the PWM type SCC efficiency value, namely 84.623% the MPPT type SCC efficiency compared to 80.935% PWM type SCC efficiency. Keywords: Solar Charge Controller, Pulse Width Modulation, Maximum Power Point Tracking